On the Development of Turkestan's National Wealth During the Colonial Period of Code Russia - S., Majidov A.; B., Jumaev J. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the fact that manuscripts and other cultural relics, which have been carefully preserved by the people for centuries, were acquired by tsarist Russia during the occupation of Turkestan by Russian troops, imperial government officials, and orient lists specially sent to the country.